Effects of service experience on customer responses to a hotel chain. Issue 1 (11th December 2018) - Bravo, Rafael; Martinez, Eva; Pina, Jose M.
Abstract : Purpose: This paper aims to analyse customer experience in a hotel and its impact on customer attitudes to both the individual hotel and the hotel chain. Specifically, the study focuses on the effects of service perceptions on emotions, satisfaction, attitude to hotel chain, intention to return, scepticism towards negative information and Word of Mouth (WOM). Design/methodology/approach: An empirical study was carried out on a sample of 300 individuals. Data were analysed through structural equation modelling. Findings: Service perceptions and emotions elicited by an individual hotel influence the customer response towards the hotel chain. Among all the outcomes considered, the strongest effects are found on WOM. Originality/value: This paper develops and empirically tests an original model that integrates the customer experience in an individual hotel and the customer response to the hotel chain. This model includes variables that have recently been considered in the literature, such as scepticism towards negative information, in combination with more traditional outcomes such as intention to return or WOM.